Rancang Bangun Aplikasi Absensi Siswa Berbasis Web Pada SMP YPUI Parung Menggunakan Metode Waterfall - Regina Pramushella, Fazha; Alifiany, Maulidiya; Octavia, Tiara; Saprudin (CV. Shofanah Media Berkah, 2024)
An attendance in an activity is in-depth and detailed information to determine the productivity or progress of the agency in general. Meanwhile, YPUI Parung Junior High School still records attendance manually. There are many shortcomings in doing attendance with manual attendance recording, including the absence of a data storage area so that it takes a long time to search for data, not to mention that there are quite a lot of students at YPUI Parung Junior High School which requires a special container to accommodate information from each number of users, manual data collection and attendance systems are impractical in the process of recording attendance to the central server and there is a possibility of errors in the recording process caused by human error and frequent loss of data due to sheets of paper. Therefore, it is necessary to have a web-based attendance application system. The method used is the waterfall method because this method allows for departremtalization and control. The development process of the one by one phase model, so as to minimize errors that may occur.